The Spiraling Case of a Yellow Chef: Isolated Hyperbilirubinemia - Karen Jiang; Ahmad Najdat Bazarbashi; Sami Dahdal; Adina Voiculescu; Natalia Khalaf (Case Reports in Hepatology)
Leptospirosis is a common bacterial disease in tropical regions of the world due to greater exposure to rodents and domestic animals; however, this condition can also occur in US urban areas, though it often goes unrecognized. Gastrointestinal symptoms are very commonly seen, and icteric leptospirosis is often confused for other conditions resulting in delayed diagnosis and worse outcomes. As mortality increases with more extensive hepatic involvement, gastroenterologists should be aware of the constellation of gastrointestinal symptoms related to leptospirosis, as it can occur in the absence of classic exposure history.